Studi Kasus Pembiasaan Menyanyi Studi Kasus Pembiasaan Menyanyikan Lagu Kebangsaan Indonesia Raya Pada Awal Pembelajaran Siswa Kelas IV SD Negeri Kota Bengkulu: Pembiasaan, Lagu Kebangsaan Indonesia Raya - Dwika Astelia; Pebrian Tarmizi (Universitas Bengkulu, 2022)
This research aimed to describe the form of habituation, the implementation of habituation and the impact of habituation of singing the national anthem; Indonesia Raya at the beginning of class for fourth grader students in elementary school in Bengkulu. This researchused case study approach as a type of qualitative research. The subjects in this study were principals, fourth grade teachers and fourth grader students. The instrument in this study were the researcher using observation sheets, interviews and documentation. The collecting data techniques used observation, interviews and documentation. The data analysis technique used an interactive model from Miles and Huberman, like collecting the data, condensing the data, presenting the data and stating the conclusions. The results showed that the form of habituation of singing the national anthem Indonesia Raya at the beginning of learning had been carried out through a form of routine habituation. In the implementation of habituation includes planning, facilities and infrastructure, implementation stage and implementation process. In addition, it was also found that the impact of the habit of singing the national anthem Indonesia Raya at the beginning of learning was the spirit of singing and the spirit of student learning. Based on the results of the study, it can be concluded that there is an effort from the principal and class teacher so that students sing the national anthem Indonesia Raya at the beginning of learning through the habituation method.